Transactional leadershipstyle on turnover intention among electrical andelectronic sub-sector employees in Malaysia - Deraman, Norita; Mad Nor, Nik Norsyamimi; Zainuddin, Nizamuddin
Job turnover is traditionally faced by organisations in many industries. Implications such as resources wastage and low productivity can be derivedfrom the turnoverissue. The turnoverintention was found to be a reliable predictor for actual turnover in previous studies. Consequently, this demands some insights on turnover intention issue, especiallywithin the Malaysiancontext. This paper will focus on determiningthe relationship of transactional leadership styles on turnover intention among manufacturing operators, particularlyin Electrical and Electronics sub-sector. The study was conductedamongst the operators of manufacturing industry in Peninsular Malaysia (N=800). Considering that Malaysia manufacturing industry has shown a strongeconomic growth through substantialinvestment in economic activities, it is essentialfor all manufacturing companies to retain talented employees and reduce the turnoverproblem in order tobe more productive and competitive. The findings had accepted the research hypothesis. Dimensions of transactional leadership styles (i.e. contingentrewards, management-by-exception passive) significantly correlated and contributed to the turnover intention. The findings hadcontributed to the theoretical significance through the examination of direct relationships between transactional leadership styles on turnover intention among local operators in the manufacturingsector in Malaysia.